MAIN TRENDS IN THE DEVELOPMENT OF MODERN CHINESE CULTURE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Until almost the beginning of the 20th century, China was a typical example of a traditional society with a specific type of saturated social dynamics. Since ancient times, cultural traditions have played the role of the most important mechanism for the integration of Chinese society and the stabilization of the reforms carried out in it. After the fall of imperial China in 1911, a series of profound political upheavals and significant social changes took place in Chinese society, during which its traditional culture was lost or forgotten. Since the end of the 20th century, China has been on the path of rapid modernization, setting itself extremely ambitious goals to become a leader in the world economy.